FAKTOR-FAKTOR YANG MEMENGARUHI NILAI PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Aditya, Kristanto; Dewi, Sofia Prima (Jurnal Paradigma Akuntansi, 2023)
This study aims to obtain empirical evidence regarding the effect of profitability, leverage, liquidity, and sales growth on firm value in manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2019 period. In this study usingpurposive sampling method and obtained 39 samples. The data processing technique uses multiple regression analysis assisted by Eviews 10 and Microsoft Excel 2016. The results of this study indicate that profitability, liquidity, and sales growth do not have a positive effect on firm value, while leverage has a positive effect on firm value. The implication of this research is to emphasize the company's operational costs followed by increased sales growth so that profits will increase and in the eyes of investors the value of the company will be good.